Bridging the gap: The impact of quality of primary care on duration of hospital stay for people with dementia. Issue 1 (15th February 2016) - Goddard, Maria; Kasteridis, Panagiotis; Jacobs, Rowena; Santos, Rita; Mason, Anne
Abstract : Purpose: – The purpose of this paper is to explore the link between one aspect of primary care in England – the annual review by general practitioners for dementia patients – and length of hospital stay (LoS). The annual review should identify the needs of both patients and carers and co-ordinate services across health and social care to address those needs. If this is done well, timely discharge from hospital may be facilitated. Design/methodology/approach: – The study uses linked national data from 2006/2007 to 2010/2011 on over 36, 000 patients, employing sophisticated statistical techniques to isolate the effect of the annual dementia review on LoS. Findings: – Hospital patients discharged to the community have significantly shorter stays if they are cared for by practices that reviewed a higher percentage of their patients with dementia. However, this effect is small and is not evident for patients discharged to care homes or who died in hospital. Longer LoS is associated with a range of co-morbidities, markers of low availability of social care and with intensive provision of informal care. Practical implications: – Although the dementia review has only a modest effect on LoS, the components of the review could improve the health and well-being of those with dementia and their carers. Originality/value: – The study is the first to employ a robust methodology to investigate the impact of the annual dementia review on hospital LoS, an important aspect of the interface between primary and secondary care. There are implications for clinical and financial aspects of health and social care policy.